THE EFFECTS OF DISSOLVED CO2 ON COAL STRUCTURE AND PROPERTIES - Larsen J.W. (My University, 2004)
Carbon dioxide dissolves in coals and swells them slightly. The dissolved CO2 seems to act as a plasticizer, enabling physical structure rearrangements and lowering the coal's softening temperature. Plasticized coals are known to rearrange to a more associated form in which fluids, including CO2, will be less soluble. A comparison of the sorption of CO2 and ethane, molecules of similar size, shows much greater CO2 uptake probably because of much faster diffusion of CO2 through the coal because CO2 readily dissolves in coals and ethane does not. Only a little is known of the effects of confining coal and lithostatic pressure on CO2 uptake and on the behavior of plasticized coals.
Keywords: COAL; CARBON DIOXIDE; SWELLING; ABSORPTION; SEQUESTRATION